GAMMA-RAY IRRADIATION EFFECT ON MECHANICAL AND DIELECTRIC PROPERTIES OF VOLCANIC BASALT MINERAL REINFORCED LOW DENSITY POLYETHYLENE FILMS - Kilic, Mehmet; Karabul, Yasar; Alkan, Umit; Yagci, Ozlem; Okutan, Murat; Okutan, Mustafa; Icelli, Orhan (OFICYNA WYDAWNICZA POLITECHNIKI WROCLAWSKIEJ, 2017)
The aim of the work is to study the mechanical and dielectric properties of low density polyethylene (LDPE) that can be modified by basalt mineral under low dose gamma irradiation. The composite films are prepared by a hot pressing method (15 MPa, 418 K, for about 10 min), and then irradiated by Co-60 gamma-rays in the dose range varied between 6 and 24 gray (Gy). Mechanical and dielectric properties of these samples are examined by means of stress-strain measurements and dielectric spectroscopy in the frequency range of 100 Hz - 15 MHz at the room temperature. Experimental measurements evidence that the mechanical properties of LDPE were weakened by basalt additives and radiation. The tensile strength of 0.5 wt.% basalt additivity, which has an optimum value increased by 30 percent when compared to pure LDPE without radiation. When LDPE and LDPE/basalt composites were radiated between 6 to 24 Gy, the mechanical properties of both samples decreased at almost the same rate. The LDPE/0.5wt.% basalt composite sample without gamma-irradiation was the one with the highest mechanical strength. In the absence of radiation, the low (static) frequency real part of dielectric constant is increased with basalt additives. The dielectric strength reached a maximum value up to 20.0 wt.% basalt additive at 6 Gy dose. However, the polymeric structure of the sample was deteriorated.
Keywords: basalt mineral; low density polyethylene; gamma irradiation; dielectric properties; mechanical properties; BETA-RELAXATIONS; ELECTRON-BEAM; COMPOSITES; TEMPERATURE; RADIATION; GLASS; Chemistry; Mining & Mineral Processing